1970
DOI: 10.6028/nbs.bss.33
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength of slender concrete masonry walls

Abstract: The Building Science Series disseminates technical information developed at the National Bureau of Standards on building materials, components, systems, and whole structures. The Series presents research results, test methods, and performance criteria related to the structural and environmental functions and the durability and safety characteristics of building elements and systems. These publications, similar in style and content to the NBS Building Materials and Structures Reports (1938-59), are directed tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…YOKEL et al [9] identified that the end support conditions of the wall, parameter also verified more recently in PETTIT et al [10], the elasticity modulus of the masonry, the shape of the bending moment diagram, and the geometric properties of the section, such as the second moment area are variables not considered in the normative criteria, but that significantly affect the masonry behavior. YOKEL et al [9] applied concepts from the formulation developed in MACGREGOR et al [11] to verify buckling of reinforced concrete columns in masonry walls. In this formulation, 40% of the product between the elasticity modulus and the second moment of area of the uncracked reinforced section was taken into account for simplified consideration of damage by cracking and loss of stiffness.…”
Section: Introduction 1buckling Criteriamentioning
confidence: 72%
See 3 more Smart Citations
“…YOKEL et al [9] identified that the end support conditions of the wall, parameter also verified more recently in PETTIT et al [10], the elasticity modulus of the masonry, the shape of the bending moment diagram, and the geometric properties of the section, such as the second moment area are variables not considered in the normative criteria, but that significantly affect the masonry behavior. YOKEL et al [9] applied concepts from the formulation developed in MACGREGOR et al [11] to verify buckling of reinforced concrete columns in masonry walls. In this formulation, 40% of the product between the elasticity modulus and the second moment of area of the uncracked reinforced section was taken into account for simplified consideration of damage by cracking and loss of stiffness.…”
Section: Introduction 1buckling Criteriamentioning
confidence: 72%
“…In this formulation, 40% of the product between the elasticity modulus and the second moment of area of the uncracked reinforced section was taken into account for simplified consideration of damage by cracking and loss of stiffness. The authors [9] also found that for unreinforced masonry only 28.5% of the uncracked stiffness can be considered. By assuming a linear distribution of normal stresses, considering total compression of the section for eccentricities (e) smaller than 1/6 of the thickness (t), YOKEL [12] published an analytical solution, Equation 1, to determine the critical load (P cr ) and the consequent lateral instability of a full section prismatic element with no tensile strength.…”
Section: Introduction 1buckling Criteriamentioning
confidence: 98%
See 2 more Smart Citations